2019
DOI: 10.1029/2019gb006223
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Internal Organic Matter is the Main Control on Pteropod Shell Dissolution After Death

Abstract: The potential for preservation of thecosome pteropods is thought to be largely governed by the chemical stability of their delicate aragonitic shells in seawater. However, sediment trap studies have found that significant carbonate dissolution can occur above the carbonate saturation horizon. Here we present the results from experiments conducted on two cruises to the Scotia Sea to directly test whether the breakdown of the organic pteropod body influences shell dissolution. We find that on the timescales of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 51 publications
(98 reference statements)
1
22
0
Order By: Relevance
“…Organisms falling through the water column may decay en route to the sediment trap, which can cause dissolution in calcareous organisms (Lohmann, 1995;Milliman et al, 1999). In pteropod shells specifically, Oakes et al (2019a) found that the majority of the postmortem dissolution was associated with the biotic decay of organic material on the inside of the shell, and therefore specimens from sediment traps do not perfectly capture in-life shell conditions. A further complication of sediment trap data is that interpretation can be skewed by the presence of "swimmers", i.e., specimens that were alive when they entered the trap (Harbison and Gilmer, 1986).…”
Section: Understanding Natural Pteropod Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Organisms falling through the water column may decay en route to the sediment trap, which can cause dissolution in calcareous organisms (Lohmann, 1995;Milliman et al, 1999). In pteropod shells specifically, Oakes et al (2019a) found that the majority of the postmortem dissolution was associated with the biotic decay of organic material on the inside of the shell, and therefore specimens from sediment traps do not perfectly capture in-life shell conditions. A further complication of sediment trap data is that interpretation can be skewed by the presence of "swimmers", i.e., specimens that were alive when they entered the trap (Harbison and Gilmer, 1986).…”
Section: Understanding Natural Pteropod Variabilitymentioning
confidence: 99%
“…Shell thickness has been used as a metric for calcification in previous studies, initially calculated from point measurements on the shell aperture from scanning electron microscope images (Bednaršek et al, 2014b;Roger et al, 2012), and later measured across entire shells from CT re-constructions (Howes et al, 2017;Oakes et al, 2019a;Peck et al, 2018). Here we use modal shell thickness to compare calcification among samples following the methods of Oakes et al (2019a). Although this method analyzes shell thickness across the entire shell, the final, or body, whorl, composed of the most recently calcified material, is the largest portion of the shell in Heliconoides inflatus pteropods ( Fig.…”
Section: The Cariaco Time Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is, therefore, an interest in monitoring pteropods over the coming decades (Bednaršek et al, 2014(Bednaršek et al, , 2017. One aspect of this monitoring could involve using CT scanning to measure the shell thickness of pteropods and assessing whether their ability to build and maintain their shells is affected by changes in ocean chemistry (e.g., Howes et al, 2017;Peck et al, 2018;Oakes et al, 2019a). Aside from their scientific interest, pteropod shells are ideal specimens to use for a CT methodology study because their overall size (< 1 mm) and the thickness of their shells (~10 µm) pushes the limits of most modern micro-CT scanners.…”
Section: Ct Scanning Thecosome Pteropodsmentioning
confidence: 99%
“…Shell volume was chosen as a comparative tool because it is sensitive to changes in scan quality, i.e., it is likely to be affected by both noise and low contrast between the different materials (shell, body, and air). Measuring pteropod shell volume in combination with shell size has practical applications as it could be used as a metric for monitoring the response of pteropods to ocean acidification in the future (e.g., Howes et al, 2017;Oakes et al, 2019a). Quality assessment method 1-SNR and CNR.…”
Section: Assessment Of Ct-scan Qualitymentioning
confidence: 99%